2006
DOI: 10.1093/treephys/26.12.1579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tapping activity on the dynamics of radial growth of Hevea brasiliensis trees

Abstract: Rubber tree (Hevea brasiliensis Müll. Arg.) radial growth dynamics were monitored with displacement sensors, together with latex production, to investigate three aspects of the dual production of latex and wood: (1) the usefulness of fine-scale dendrometric measurements as a physiological tool to detect water shortage through radial growth; (2) the dynamic aspects, both at the seasonal and at the multi-year scale, of the competition between latex and wood production; and (3) the spatial distribution of radial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 34 publications
0
33
0
9
Order By: Relevance
“…In a study conducted by Silpi et al (2006) on a rubber tree Hevea brasiliensis, tapped trees showed 50%…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Silpi et al (2006) on a rubber tree Hevea brasiliensis, tapped trees showed 50%…”
Section: Discussionmentioning
confidence: 99%
“…The possible effects of ethephon on metabolism and water flow are not without danger for the tree. If increased resources are diverted towards gum yield, this may have detrimental effects on tree growth and tree resistance to adverse conditions (Silpi et al 2006). The indiscriminate use of ethephon following the discovery of its effect on yield has induced many physiological disorders in rubber trees, from the reversible ''Tapping panel dryness'' due to fatigue to the irreversible ''Bark necrosis'' symptoms (D'Auzac et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the rate of latex coagulation in H. brasiliensis (with low PPO activity) and T. kok-saghyz (with high PPO activity) is very similar, indicating that other factors contribute to the coagulation of H. brasiliensis latex. Some of these factors have recently been identified (Gidrol et al, 1994;Silpi et al, 2006).…”
Section: Ppo Silencing Affects Latex Coagulation Inmentioning
confidence: 99%